The Impact of Music Games on the Social Interaction of Elderly Occupants in the Communal Room of a Nursing Home - Taufik, Yusaumi Ramadhanti Fitri; Wardono, Prabu; Adhitama, G. Prasetya (UI Scholars Hub, 2018)
Being elderly is a stage of life characterized by physiological, psychological and social maturity, and degradation. Initial observation has revealed that the elderly rarely interact with other elderly people in communal rooms and activities. Furthermore, they tend to enjoy activities related to music the most. The presence of a stimulus based on hobbies in a communal room through a music game was expected to revitalize spatial function and increase the elderly’s life quality. The purpose of this study was to analyze the impact of a music game and identify the elements thereof, which can influence the elderly’s social interaction in a communal room. A quasi experiment was employed and the results were analyzed using Wilcoxon Signed Rank statistics test. The results revealed that communal rooms can function as social space by implementing a music game. Music has an impact on the elderly’s social interaction in relation to the time they wish to play, their willingness to invite other elderly people, the type of social contact, duration of interaction, and the number of participants. The choice of a video clip game is an element of a music game, which had a dominant effect on their social interaction in comparison to the choice of singers’ pictures and lyrics of notes games.